Trauma and cinema : cross-cultural explorations - Kaplan, E. Ann; Wang, Ban, 1957- (Hong Kong University Press, 2004)
Annotation This volume addresses the relation of trauma to transnational modern mass media. the first of its kind, Trauma and Cine.
Keywords: Motion pictures -- History.; Traumatism.; War victims.; Cinéma -- Histoire.; Traumatisme.; Victimes de guerre.; PERFORMING ARTS -- Film & Video -- Reference.; SOCIAL SCIENCE -- Anthropology -- Cultural.; Motion pictures; Traumatism; War victims; Film; Psychisches Trauma -- Motiv; History; Aufsatzsammlung.